Принципи сюжетної та образної організації міського простору в романі С. Андрухович «Фелікс Австрія» - Штогрин, Мар'яна; Shtohryn, Mariana (Східноєвропейський національний університет імені Лесі Українки, 2015)
Автор статті розглядає міфологічний дискурс міста Станіславова у романі Софії Андрухович «Фелікс Австрія». Виявлено соціально-стратифікаційну структуру Станіславова як відображення сюжетної організації твору. Показано вплив міста на формування свідомості його мешканців. The author of the paper examines the mythological discourse of Stanislaviv in Sofiia Andrukhovych's novel "Felix Austria". Social and stratified structure of Stanislav as a reflection of the narrative structure of the novel is determined. The influence of the city on the formation of consciousness of its inhabitants is described. The author builds a special time-space, simulating it with fragments of impressions, dreams in reality, memories and ideas, illusions game, combining elements of mystical and realistic. Formation of consciousness of the urban residents is directly related to the construction of social and stratification structure of the city and defines the plot structure of the novel. The main feature of image-creating in the novel "Felix Austria" is presented through women's outlook in terms of contemporary, who is influenced by the ideas of feminism. The plot-compositional organization of the novel is determined by the unconformity of the situation as it unfolds, with the estimates it receives in the perception of the novel's characters.
Principles of the Narrative Organization of the Urban Space in the Novel of Sofiia Andrukhovych "Felix Austria"
Keywords: місто-міф; хронотоп; city-myth; chronotope